Influencing Factors of Online Shopping on Customer Satisfaction in Birendranagar, Surkhet - Pulami, Hasta Bahadur (Journal of Nepalese Management and Research, 2023)
This research aims to investigate and assess the variables that affect the impact of Internet shopping on consumers’ satisfaction in Birendranagar, Surkhet. This research used a causal-comparative design to ascertain the causes and consequences of specific variables. One hundred fifteen customers who used to shop online provided information for the analysis. Multiple regression, F-test, mean, and standard deviation were used in the studies. According to the survey, there is a statistically significant impact of perceived risk, comfort, ease, and competitive price when it comes to customer satisfaction. However, it was discovered that the effects of each variable separately produced distinct outcomes. Customer satisfaction is significantly impacted (<.05) by comfort and perceived risk but not significantly by competitive pricing and shopping convenience.